Collaborative Music Creation Method Based on Image Collection of Lattice Code - Yuehua Xiang (International Transactions on Electrical Energy Systems)
With the development of science and technology, more and more emerging technologies have been integrated into electronic music, forming a rich and diverse form of interactive electronic music. This research mainly discusses the collaborative music creation method based on bit matrix code image acquisition. In the decoding process, the displacement value of each point should be determined according to the direction and distance from the point to the reference point of the corresponding grid raster. This article marks the position characteristics of image symbols according to the dot matrix code notation defined in the improved coding method. After searching for a pair of dot codes with the shortest distance in the horizontal or vertical direction, starting from the first code point in the vertical direction and following the second code point. Through the above method, it is possible to accurately construct the grid raster lines of the dot matrix position encoding symbol image formed after the improved encoding, so that the decoding of the dot matrix symbol image is more accurate, and the composition translation is reduced. The improved coding method reduces the error of the origin matrix code by about 0.11 mm as a whole. This research will realize the collaborative recording of data in the music creation process, which will bring great convenience to creators.